Establishment of a multiplex pcr assay for simultaneously detecting two target sequences of Chlamydia trachomatis - Thang, Nguyen Nam; Do, Bui Duc; Hoa, Nguyen Thi; Hoa, Tran Thi; Quang, Phan Ngoc; Dung, Bui Huong; Quyen, Dong Van (Academia Journal of Biology, 2016)
PCR is a technique commonly applied in screening urogenital tract infections caused by Chlamydia trachomatis (CT). Since some CT strains might not have plasmid, the PCR technique using DNA plasmid sequence as target would produce false negative results. This study developed a multiplex PCR (mPCR) assay that could detect both DNA plasmid and omp1 gene sequences of CT in order to avoid these false negative results. Originally, 7 primer pairs were designed based on DNA plasmid and omp1 gene sequences of CT. After being tested in different conditions, two primer pairs CTM-F1R1 and CTP-F1R2 were finally selected to be used in the mPCR assay that could simultaneously detect specific sequences on DNA plasmid (434 bp) and on omp1 gene (153 bp). CT could be detected by mPCR if there were 5 or more copies of omp1 gene and/or 5 or more copies of plasmid in suspected samples. The assay was tested on 128 endocervical swab specimens and the results were then compared with those of 2 other PCR assays. Sensitivity, specificity, positive predictive value, negative predictive value of the mPCR assay were all 100%. Additionally, this assay could eliminate false negative results of CT strains which do not contain plasmids. Thus, the developed assay might be applied in diagnosis and/or screening CT in the community. Citation: Nguyen Nam Thang, Bui Duc Do, Nguyen Thi Hoa, Tran Thi Hoa, Phan Ngoc Quang, Bui Huong Dung, Dong Van Quyen, 2017. establishment of a multiplex pcr assay for simultaneously detecting two target sequences of Chlamydia trachomatis. Tap chi Sinh hoc, 39(1): 108-114. DOI: 10.15625/0866-7160/v39n1.8396. *Corresponding author: nnthang_tmu@yahoo.com.vn. Received 21 September 2015, accepted 20 March 2017